An updated catalogue of Agrypninae (Coleoptera: Elateridae) from Pakistan - Hoffmannova, Johana; Packova, Gabriela; Prosvirov, Alexander S.; Akhter, Muhammad Atique; Kundrata, Robin (Zootaxa, 2023)
The updated catalogue of Agrypninae from Pakistan is provided. We list 86 described species classified in 18 genera and five tribes (Agrypnini, Drilini, Hemirhipini, Oophorini, and Pseudomelanactini). More than one third of species are currently endemic to Pakistan. For each species we provide information on distribution and relevant bibliography. The following new combinations are proposed for species hitherto included in Conoderus Eschscholtz, 1829 (since Conoderus is currently a synonym of Monocrepidius Eschscholtz, 1829): Monocrepidius aeolodermoides (Platia, 2015) comb. nov., Monocrepidius cylindricus (Platia & Ahmed, 2016) comb. nov., Monocrepidius drasterioides (Platia & Ahmed, 2016) comb. nov., Monocrepidius nigromaculosus (Vats & Chauhan, 1992) comb. nov., Monocrepidius mithiensis (Platia & Ahmed, 2016) comb. nov., and Monocrepidius vartiani (Platia, 2015) comb. nov. Additionally, Conoderus pakistanicus Mangi, Pahnwar & Shaikh, 2022 is synonymized with Lanelater bipunctatus (Candèze, 1857).